FORMING A HEALTHY LIFESTYLE IN THE FAMILY - Atamurodov , Shodiyar Oralovich; Hasanov , Anvar Toxirovich (Innovative Development in Educational Activities, 2023)
The article describes how children form a healthy lifestyle in the family.